2021
DOI: 10.3390/molecules26144316
|View full text |Cite
|
Sign up to set email alerts
|

Fe3O4/Graphene Composite Anode Material for Fast-Charging Li-Ion Batteries

Abstract: Composite anode material based on Fe3O4 and reduced graphene oxide is prepared by base-catalysed co-precipitation and sonochemical dispersion. Structural and morphological characterizations demonstrate an effective and homogeneous embedding of Fe3O4 nanoparticles in the carbonaceous matrix. Electrochemical characterization highlights specific capacities higher than 1000 mAh g−1 at 1C, while a capacity of 980 mAhg−1 is retained at 4C, with outstanding cycling stability. These results demonstrate a synergistic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…Composite anode material based on Fe 3 O 4 and reduced graphene oxide was prepared by base‐catalysed co‐precipitation and sonochemical dispersion. Electrochemical characterization highlights specific capacities higher than 1000 mAh g −1 at 1 C, while a capacity of 980 mAhg −1 was retained at 4 C, with outstanding cycling stability [19] …”
Section: Outcomes Of the Projectmentioning
confidence: 99%
See 1 more Smart Citation
“…Composite anode material based on Fe 3 O 4 and reduced graphene oxide was prepared by base‐catalysed co‐precipitation and sonochemical dispersion. Electrochemical characterization highlights specific capacities higher than 1000 mAh g −1 at 1 C, while a capacity of 980 mAhg −1 was retained at 4 C, with outstanding cycling stability [19] …”
Section: Outcomes Of the Projectmentioning
confidence: 99%
“…Electrochemical characterization highlights specific capacities higher than 1000 mAh g À 1 at 1 C, while a capacity of 980 mAhg À 1 was retained at 4 C, with outstanding cycling stability. [19] Thanks to its high theoretical capacity, abundant availability and respect for the environment, silicon has been proposed as a possible alternative to graphite. Already in the previous threeyear program this material had been studied even reaching the realization of a complete battery.…”
Section: Innovative Electrode Materials For Li-and Na-ion Batteriesmentioning
confidence: 99%
“…In order to improve the fast-charging performance, some novel anode materials such as metal oxides(flaky �-Fe 2 O 3 , [99][100][101] Co 3 O 4 , [102,103] CoFe 2 O 4 , [104] Nb 2 O 5 nanoparticles [105] ), MXene, [106,107] Si nanofibers, [108] Sn nanoparticles, [109] and Ge nanoparticles [110] have been developed. M. T. Sougrati et al [111,112] studied the electrical properties of TiSnSb anode material which showed a reversible capacity of 540 mAh g À 1 .…”
Section: Other Novel Anode Materialsmentioning
confidence: 99%
“…[11] Graphene as a support material for metal oxide nanoparticles not only improves the anode performance by improving the electronic and mechanical properties but also leads to new physical and electrochemical properties arising due to the synergistic effect that graphene or metal oxide alone cannot exhibit. [14] Hence, the capacity and cycling performances of fabricated metal oxide/graphene composites as anodes for lithium-ion batteries were investigated. [15] Wu et al prepared different hollow and solid bimetal oxide-graphene composite electrodes and found that CoFe 2 O/RGO composite exhibits excellent rate capability and high-rate cycling stability for lithium storage due to their stable, rigid structure.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, preparing graphene‐metal oxide composite or coated anodes is an effective approach for increasing anode capacity by combining both insertion/de‐insertion and conversion mechanisms and improving cycle stability by buffering volume expansion [11] . Graphene as a support material for metal oxide nanoparticles not only improves the anode performance by improving the electronic and mechanical properties but also leads to new physical and electrochemical properties arising due to the synergistic effect that graphene or metal oxide alone cannot exhibit [14] . Hence, the capacity and cycling performances of fabricated metal oxide/graphene composites as anodes for lithium‐ion batteries were investigated [15] .…”
Section: Introductionmentioning
confidence: 99%